O catolicismo midiático: a evangelização do Padre Fábio de Melo - Mendonça, Henriete Cabral (2013)
The purpose of this research is to analyze Father Fabio de Melo´s media resources and his production of symbolic goods as a representative of the Catholic media. It also seeks to analyze Catholic Church social communication which flags a Catholicism media in order to maintain hegemony among other religions; identify the comprehensiveness of the media resources of this priest as a strategy to reassert and stimulate Catholicism media, and check the stress tensions in the appreciation of the artistic performance over the traditional role of a priest. It starts with the premise that the activities of this Clergy stress a contemporary Catholic priesthood, with significant inclusion in the religious and laical media, and expanding frontiers of this type of Catholicism in the logic of the market. In other words, this agent´s symbolic goods and media resources reinforce a new ´style of priest´, composed from a media priesthood habitus. It hilights his appearances as a celebrity with an emphasized televisibility, which are his brand spirit. Finally, we focus how virtual communities in cyberspace prove the legitimacy of Father Fabio de Melo´s media production in modern religious field, which meets the logic of Catholicism media and complies the industrial cultural standards.